Geomorphology, sedimentology, and hazard assessment of the Sapta Koshi alluvial fan in eastern Nepal - Thakur, Pramod Kumar; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2002)
The Sapta Koshi River that is known for exceptionally high sediment-carrying and channel-shifting nature forms a broad alluvial fan into the Indo-Gangetic Plain after its emergence from the Siwalik Hills. The Sapta Koshi alluvial fan has a radial length of about 45 km and width of about 15 km in the Nepalese territory, where it forms a proximal to midfan segment extending from NE to SW, showing various geomorphic surfaces characterised by gravel to fine sand and mud lithofacies associations. The alluvial fan deposits are of Holocene epoch, and are unconsolidated and vulnerable to rapid erosion. Flooding, river oscillation and soil erosion are the main environmental problems in the alluvial fan region. The flood hazard assessment was made using criteria such as slope, relative relief, distance from the active channel and its shifting pattern, engineering protection-structures, and man-induced activities. The alluvial fan region was zoned into three hazard levels such as high, medium and low. The western bank of the Sapta Koshi River, around Balardaha. Bhardaha, and HanumanNagar are identified to be highly prone to flooding and waterlogging. Man-induced activities play important role in increasing the hazard level in these areas. Therefore, short- and long-termed preventive measures have been suggested.